Finite Element Method with Applications in Engineering. - Desai, Y. M.; Eldho, T. L.; Shah, A. H. (2011)
Finite Element Method with Applications in Engineering presents a practical understanding of the finite element method with a variety of engineering applications that will aid students, teachers, practicing engineers and researchers. It begins with an introduction to the mathematical modeling of engineering problems and approximate methods of analysis. It then introduces the different approaches in FEM such as direct approach, principle of virtual work, variational principle and method of weighted residual. Finally, the applications of FEM to real-world problems are presented in 1D, 2D and 3D for structural analysis, heat and mass transfer, geo-mechanical, fluid flow and other problems. Suitable for engineering students and professionals.
10.6.2 Governing Equations and Boundary Conditions -- 10.6.3 Finite Element Formulation -- 10.6.3 Case Study -- 10.7 FEM-Software and Web Resources -- 10.7.1 Introduction -- 10.7.2 FEM in Structural Engineering -- 10.7.3 FEM in Geotechnical Engineering -- 10.7.4 FEM in Fluid Mechanics -- 10.7.5 FEM in Thermal and Automobile Engineering -- 10.7.6 FEM in Physics -- 10.7.7 Multi-Field FEM Software -- 10.7.8 FEM in Other Fields -- 10.8 Concluding Remarks -- References and Further Reading -- Appendix A: Review of Matrix Algebra and Matrix Calculus -- Appendix B: Elements of Calculus of Variations -- Appendix C: Example Illustrating Use of Galerkin's Method -- Appendix D: Review of Gauss Quadrature Procedure for Numerical Integration -- Appendix E: User's Manual For the Simplified Finite Element Analysis Program (sfeap) -- Appendix F: Graphical Interface For the Simplified Finite Element Analysis Program (sfeap) -- Appendix G: Computer Programs for One-Dimensional and Two-Dimensional Problems -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books